2021
DOI: 10.1002/jtr.2488
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising risk in cruise holidays: A critical review

Abstract: The knowledge base for cruise holidays is conceptually underdeveloped and narrowly focused on health and safety and environmental concerns. This critical review of risk research in relation to ocean cruising identifies knowledge gaps revealing the significance of factors such as financial, performance, time-loss, opportunity, functional, social and psychological risk. This review calls for a wider conceptualisation of risk that moves beyond an emphasis on physical risk. A deeper understanding of risk in ocean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 147 publications
(243 reference statements)
1
2
0
Order By: Relevance
“…Our findings also indicate a demographic shift among traditional cruisers with older cohorts being less likely to cruise. This finding resonates with that of Holland, Weeden, et al (2021) and Pappas (2021) whose studies both revealed that older segments felt more at risk and more vulnerable to COVID-19 compared with younger cohorts. Older segments in our study also proved to be more price sensitive.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings also indicate a demographic shift among traditional cruisers with older cohorts being less likely to cruise. This finding resonates with that of Holland, Weeden, et al (2021) and Pappas (2021) whose studies both revealed that older segments felt more at risk and more vulnerable to COVID-19 compared with younger cohorts. Older segments in our study also proved to be more price sensitive.…”
Section: Discussionsupporting
confidence: 81%
“…Also, the global tourism industry is facing enormous damages due to the COVID-19 pandemic (Perić et al, 2021). The COVID-19 pandemic has brought even greater attention to risk and its perception within the travel industry calling for further research on the perception of risk by tourists to close critical gaps (Holland et al, 2021). Individuals perceive risks associated with COVID-19 differently, and this will have an impact on their willingness to travel.…”
Section: Perceived Travel Risks Of Senior Citizensmentioning
confidence: 99%
“…Functional risk in a hotel context indicates this area is not clearly understood concerning holiday decision-making; it is a significant gap considering the relative frequency of such events, and the numerous ways mechanical or equipment failure can occur. Similarly, Changes caused by mechanical faults harm tertiary service providers such as hotels, airlines, ground transportation and port services (Holland et al, 2022). Hence the following hypothesis was proposed: H4: Functional risk affects consumers' repeat purchase intention to the same hotel.…”
Section: Functional Riskmentioning
confidence: 99%